The Anticicrobial screening of a Barbadian medicinal plant with indications for use in the treatment of diabetic wound infections - Carrington, S. [et al] (2012)
Presents the results of investigation to test the ability of Justicia secunda (Bloodroot) used in folklore for wound healing, to aid diabetic wound healing by antimicrobial activity.